Effectiveness Of Zakat Collection In Optimizing The Potential Of Zakat In West Java Case Study Of West Java Baznas - Ahmad Syakir; Lutfi Zulkarnain (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2019)
This study aims to analyze the strategic effectiveness of Zakat collection carried out by West Java BAZNAS. In this study the author uses a qualitative approach, with data collection techniques that are descriptive analysis. The data used in this study were obtained from the results of observations at the place of research, direct interviews with related sources, and collection of documentation as data collection techniques in this study. The results and findings of this study indicate that the collection of zakat made has a decrease. Where there are internal factors of West Java BAZNAS that have not been optimal and public awareness in carrying out zakat is still low. This research is expected to be a reference for zakat institutions, academics, and the public about the need for support in collecting zakat.